OpenADAM: an open source genome-wide association data management system for Affymetrix SNP arrays - Yeung, J MY; Sham, P C; Chan, A SW; Cherny, S S (BMC genomics, 2008)
Background Large scale genome-wide association studies have become popular since the introduction of high throughput genotyping platforms. Efficient management of the vast array of data generated poses many challenges. Description We have developed an open source web-based data management system for the large amount of genotype data generated from the Affymetrix GeneChip ® Mapping Array and Affymetrix Genome-Wide Human SNP Array platforms. The database supports genotype calling using DM, BRLMM, BRLMM-P or Birdseed algorithms provided by the Affymetrix Power Tools. The genotype and corresponding pedigree data are stored in a relational database for efficient downstream data manipulation and analysis, such as calculation of allele and genotype frequencies, sample identity checking, and export of genotype data in various file formats for analysis using commonly-available software. A novel method for genotyping error estimation is implemented using linkage disequilibrium information from the HapMap project. All functionalities are accessible via a web-based user interface. Conclusion OpenADAM provides an open source database system for management of Affymetrix genome-wide association SNP data.